DI BALIK TEKANAN KERJA RITEL: PENGARUH PERCEIVED SOCIAL SUPPORT TERHADAP PERCEIVED STRESS - R. Alguskha Nalendra PS; Nita Rohayati; Ananda Saadatul Maulidia (Penerbit Goodwood, 2026)
Purpose: This study examines the effect of perceived social support on perceived stress among employees of a fashion accessory retail company in Indonesia, addressing the limited evidence on this relationship among Indonesian retail workers.Research Methodology: A quantitative, non-experimental, cross-sectional causal-associative design was employed. Data were collected through an online survey of 369 employees using the Perceived Stress Scale-10 (PSS-10) and the Multidimensional Scale of Perceived Social Support (MSPSS). Simple linear regression was used to analyze the data.Results: Extending previous studies that primarily focused on job stress, this study examines perceived stress as a broader psychological outcome influenced by both work- and non-work-related stressors. The findings revealed that perceived social support had a significant negative effect on perceived stress (B = -0.119, p < 0.001). The relationship was weak (R = -0.264), and perceived social support explained 7% of the variance in perceived stress (R² = 0.070), indicating limited explanatory power.Conclusions: Higher perceived social support is associated with lower perceived stress among retail workers. However, its relatively small effect suggests that perceived stress is influenced by multiple psychological and organizational factors beyond social support.Limitations: The cross-sectional design and the use of respondents from a single fashion accessory retail company limit causal inference and the generalizability of the findings.Contributions: This study provides empirical evidence from the Indonesian retail sector by highlighting perceived stress, rather than job stress, as an outcome of perceived social support, offering practical insights for workplace stress management.